Biomass and Yield in Solanum lycopersicum Expressing a Synthetic Photorespiration Pathway - Laura Dougherty; Bret Cooper; James Bunce; Bryan Vinyard; John Stommel (Journal of the American Society for Horticultural Science)
Considerable interest exists in improving the efficiency of photosynthesis and photorespiration to increase crop yields that will address growing world food needs. The current study investigated whether a novel synthetic photorespiratory pathway demonstrated to reduce photorespiratory metabolic energy demands and increase plant vegetative biomass in model species could boost tomato crop yield, notably yield of marketable fruit. The tomato cultivar Moneymaker was transformed with a synthetic photorespiration pathway construct containing a Cucurbita maxima malate synthase (MS) gene and a Chlamydomonas reinhardtii glycolate dehydrogenase (CrGDH) gene targeted to the chloroplast, with a plastid glycolate-glycerate translocator 1 (PLGG1) hairpin interference construct targeting the native photorespiratory pathway. Plants of seven T2 generation lines from independent transformation events expressed the MS and CrGDH transgenes, while having at least 3-fold reduction of native PLGG1 expression relative to non-transformed Moneymaker. Plants from transformed lines were larger and exhibited up to 63% increased biomass in comparison with the Moneymaker control. The number of fruit was similarly greater (1.4- to 4.2-fold) in modified plants; however, average individual fruit weights were significantly less for all but one line. Among transformed lines, larger fruited lines had the lowest biomass, while the smaller fruited lines had the highest biomass. Values for VCmax and Jmax derived from CO2 assimilation curves were statistically similar or lower in transformants relative to the control. Metabolic profiles obtained from high-performance liquid chromatography mass spectrometry (HPLC-MS) analysis revealed increases in forms of inactivated auxin. Principal component analysis of metabolite profiles separated transformants into two groups distinguished by total biomass and fruit size. Observed increases in plant biomass in transformed lines suggests that energy savings were realized from reduced photorespiration but were directed toward vegetative growth. Further studies to balance vegetative vs. reproductive biomass and exploit higher fruit counts observed in transformants may be beneficial for enhanced fruit yield.